Exploring The Illocutionary Act In “The Beekeeper” (2024) By David Ayer - Rosalinah, Yanti; Hakim, Aulia; Fazari, Tengku Nizar (Sean Institute, 2025)
This research analyzes the illocutionary acts of Adam Clay, the protagonist in The Beekeeper (2024), through the lens of John Searle’s Speech Act Theory. The objective is to explore how these acts contribute to character development and thematic elements of justice, revenge, and morality. Utilizing a qualitative content analysis methodology, dialogues from critical scenes were transcribed and categorized into Searle’s classifications: assertives, directives, commissives, expressives, and declaratives. The findings reveal a predominance of assertive acts (30 occurrences, 30%), followed by directives (25 instances, 25%), commissives (20 instances, 20%), expressives (15 instances, 15%), and declaratives (10 instances, 10%). This distribution underscores Clay’s assertive control and emotional complexity, enhancing the film's thematic richness. In conclusion, the study highlights the pivotal role of language as a narrative device in The Beekeeper, demonstrating how illocutionary acts encapsulate the protagonist's motivations and ethical dilemmas. This research contributes to the understanding of pragmatic analysis in cinematic contexts and sets a foundation for future investigations into the interplay between language and character development in film.